Rejecting Alternative Dispute Resolution (ADR) in Sexual Violence Crime Cases - Kusuma, Wisnu Wardana; Rika Sandria Putri; Afnan Rifai Sulistyo; Ika Dewi Sartika Saimima (Journal of Law, Politic and Humanities, 2023)
The crime of sexual violence in Indonesia is in an emergency phase. The massive number of reports of cases of sexual violence has created its own paranoia for the community, especially in terms of the process of handling cases of sexual violence in Indonesia. This study aims to analyze cases and phenomena of sexual violence in Indonesia and to carry out a normative approach as a study of handling cases of sexual violence. The research method used is normative legal research and the method of analyzing literature and case studies of sexual violence in Indonesia. The results of this study indicate that cases of sexual violence have evolved along with the times. The emergence of gender-based cyber sexual violence (KSBG), abortion cases, and efforts to handle cases using the Alternative Dispute Resolution (ADR) system are injustices to victims. Settlement of cases of sexual violence must be in accordance with Law Number 12 of 2022 concerning Crimes of Sexual Violence, namely the implementation of a legal judicial process.